Synthesis, biological evaluation, and molecular docking of novel hydroxyzine derivatives as potential AR antagonists - Qi, Yueheng; Xue, Baoli; Chen, Shijin; Wang, Wang; Zhou, Haifeng; Chen, Hong (Frontiers in Chemistry, 2022)
Prostate cancer (PCa) is a malignant tumor with a higher mortality rate in the male reproductive system. In this study, the hydroxyazine derivatives were synthesized with different structure from traditional anti-prostate cancer drugs. In the evaluation of in vitro cytotoxicity and antagonistic activity of PC-3, LNCaP, DU145 and androgen receptor, it was found that the mono-substituted derivatives on the phenyl group (4, 6, 7, and 9) displayed strong cytotoxic activities, and compounds 11–16 showed relatively strong antagonistic potency against AR (Inhibition% >55). Docking analysis showed that compounds 11 and 12 mainly bind to AR receptor through hydrogen bonds and hydrophobic bonds, and the structure-activity relationship was discussed based on activity data. These results suggested that these compounds may have instructive implications for drug structural modification in prostate cancer.